Consumo de alimentos processados e ultraprocessados por crianças de 13 a 35 meses e fatores associados - Batalha, Mônica Araujo (2016)
INTRODUCTION: Healthy eating habits started from the earliest years of life are critical to growth and development of children. However, the ultra-processed products are being introduced early on children's diets and little is known about the determinants of this consumption. OBJECTIVES: To evaluate the consumption of processed and ultra-processed foods (PUP) among children of 13-35 months and associated factors. METHODS: We studied 1185 children, participants following the BRISA cohort in São Luís, Maranhão. Food consumption was investigated using the Food Survey Recall 24h and the percentage of daily caloric intake and nutrients were estimated by groups of food, classify according with the type of processing used in their fabrication. We used Poisson regression model with robust variance estimation and hierarchical approach to estimate the prevalence ratios (PR) of variables associated with high consumption of processed and ultra-processed foods. RESULTS: Mean energy consumption were 1226 kcal/day. After the adjusted analysis, there was a higher proportion of high consumption of PUP among children whose mothers had less than or equal to 8 years of study (PR 1.32; 95% CI: 1.05-1.67), 9 to 11 years of study (PR 1.24; 95% CI: 1.02-1.51) and among those who had more than 18 months of life (PR 1.29; 95% CI: 1.09-1.52). CONCLUSIONS: The knowledge of the factors related to high consumption of PUP in childhood is critical to the direction of intervention and prevention actions, targeting both mothers and children, in order to strengthen the acquisition of healthy habits early.